Flow in a pipeline with leakage - Izani, Siti Nur Haseela (2013)
Leakage in pipelines has always been one of the main problems in pipelines transportation fluid. This fluid leakage can happened without any warning. The leaking of fluid in pipeline can give effects to the economic loss and environmental risk. Therefore, the early detection of leak is a main role in the fluid transportation pipelines. This paper presents a technique for early detection of leak in single pipe. The fluid pressure and flow rate velocity are considered as two dependent variables. The governing equations of transient flow were proposed. The mathematical formulation describes the solution process and then solved by the Method of Characteristics and Finite Different Method (FDM). The simulation of pipeline leakage with the three different diameters has been carried out by Matlab programming to see the behavior of pressure and flow in the upstream head and downstream head when leakage occurs. The results show; flow rate trends at the incoming fluid flow pipelines is not equal to outgoing fluid pipelines when leaking occurs and pressure trend at the incoming fluid also not equal to pressure trend outgoing fluid. These situations are obtained to indicate the early presence of leakage. This method provided a theoretical basis for early recognizing leakage